Front Cover: Control of lipid metabolism by the dynamic and nutrient‐dependent post‐translational modification O‐GlcNAcylation. Issue 2 (14th April 2023) - Schulz, Céline; Lemaire, Quentin; Berthier, Alexandre; Descat, Amandine; Kouach, Mostafa; Vercoutter‐Edouart, Anne‐Sophie; Yazidi‐Belkoura, Ikram El; Hardivillé, Stéphan; Goossens, Jean‐François; Lefebvre, Philippe; Lefebvre, Tony
Abstract : Post‐translational modifications act as rheostats of protein activity. Many of them reflect environmental variations and allow the cell to give an adapted response to these changes. In this cover article #Ref, Céline Schulz and collaborators provide an in‐depth overview of the still underrated role of the nutrient‐dependent post‐translational modification O‐GlcNAcylation in the regulation of the metabolism of lipids, a very heterogenous family with very diverse functions.